PERIOPERATIVE ANESTHETIC MANAGEMENT IN LIPOSUCTION SURGERY - Septiani, Gusti Ayu Pitria; Nasrani, Cindy Henrietta (DiscoverSys Inc., 2018)
Liposuction or lipoplasty is one of the most popular treatment modalities in aesthetic surgery which brings the certain unique anesthesia considerations. The patient should be assessed by the same standards as anyone else who is undergoing any surgery including a complete preoperative history and physical examination. The patients undergoing major liposuction procedure have a greater associated comorbid condition with the incidence of obesity. Moreover, intraoperative fluid management in liposuction procedure is also different from other surgeries where this procedure has the higher risk for fluid overload. Some complications related to liposuction are pulmonary thromboembolism, fat embolism syndrome, and anesthesia-related complications. This case report describes an obese class I (BMI >30.3 kg/m2) patient who was undergoing an elective tumescent liposuction surgery under general anesthesia. During surgery, this patient received total subcutaneous infiltration of 1,200 mL tumescent solution and the total lipoaspirate was 3,300 mL. The surgery was uneventful without any certain complication. The anesthetic management of liposuction includes the preoperative evaluation, with particular attention to anything that might predispose the patient to complications, being essential to avoid unwanted occurrences.